Analysis of the concentrations of eotaxin 1/CCL11, eotaxin 2/CCL24 and eotaxin 3/CCL26 in the serum of adult patients with atopic dermatitis - Owczarek, Witold; Paluchowska, Elwira Beata; Targowski, Tomasz; Nawrocka, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction. Eosinophils play an important role in development of allergic diseases. Recent studies indicate their many relevant functions in the development of allergic inflammation related to both an effector and immunomodulatory role. The recognition of factors responsible for eosinophil recruitment to tissues may be significant for understanding allergic diseases’ regulatory processes, including mechanisms leading to skin changes in atopic dermatitis (AD). The most prominent chemotactic factors influencing eosinophil accumulation are those acting selectively via the CCR3 eotaxin receptor. Many reports indicate a relevant role of these chemokines in pathogenesis of allergic diseases. Objective . To measure the level of serum concentrations of eotaxin 1/CCL11, eotaxin 2/CCL24 and eotaxin 3/CCL26 in AD patients and healthy subjects in relation to disease intensity assessed by the SCORAD scale. Material and methods . Hundred and one AD patients and 21 healthy subjects as the control group were investigated. The concentrations of eotaxin 1/CCL11, eotaxin 2/CCL24 and eotaxin 3/CCL26 were measured using enzyme-linked immunosorbent assay (ELISA) with R&D Systems kits (USA). Results . It was found that in the group of AD patients the average serum concentration of 1/CCL11 eotaxin was 123.86 pg/ml. The average serum concentration of 2/CCL24 eotaxin was 1064.52 pg/ml and of 3/CCL26 eotaxin 16.93 pg/ml. In healthy volunteers (control group), the mean serum concentration of 1/CCL11 eotaxin was 195.64 pg/ml, the mean serum concentration of 2/CCL24 eotaxin was 965.58 pg/ml, and of 3/CCL26 eotaxin 0.79 pg/ml. Comparative analysis of serum eotaxin levels between the group of AD patients and the healthy controls showed that the mean serum concentration of 1/CCL11 eotaxin in patients with atopic dermatitis is significantly lower (p = 0.002), and of 3/CCL26 eotaxin higher (p = 0.0000001) than in healthy controls. In the group of AD patients the average severity of illness rated with the SCORAD scale was 53.17. Regression analysis between the exacerbation of disease rated with the SCORAD scale and serum levels of 1/CCL11 eotaxin, 2/CCL24 eotaxin and 3/CCL26 eotaxin showed a statistically significant correlation for all measured parameters (respectively p = 0.001, p = 0.01, p = 0.00001). Conclusions . The analysis of results showed that in the researched group: 1. Mean eotaxin 3/CCL26 and eotaxin 2/CCL24 serum concentration is higher in AD patients as compared to healthy subjects and in the case of eotaxin 3/CCL26 the difference is statistically significant. 2. Mean eotaxin 1/CCL11 serum concentration is statistically lower in AD patients as compared to healthy subjects. 3. Eotaxin 1/CCL11, eotaxin 2/CCL24 and eotaxin 3/CCL26 serum concentrations correlate with AD intensity assessed by SCORAD.